Свободные и вынужденные колебания трехслойных круговых пластин на упругом основании - Кубенко, В.Д.; Старовойтов, Э.И.; Леоненко, Д.В. (Геотехническая механика, 2009)
Досліджено осесиметричні коливання пружної кругової тришарової пластини на
пружній основі під дією локальних поверхневих навантажень. Реакція основи описується моделлю Вінклера. Для опису кінематики несиметричного по товщині пакету прийнято гіпотези ламаної нормалі. Заповнювач - легкий. Отримано аналітичні рішення задачі і проведений їх чисельний аналіз. The axisymmetrical vibrations of elastic circular sandwich plate on elastic foundation under local shape loading influence are explored. Reaction of foundation was described on the base of
Winkler’s model. For the kinematics description asymmetrical on the thickness of package accepted hypotheses broken normal. Filler is light. Analytical deciding a problem are received and their numeric analysis are conducted.